Evolutionary stress minimisation on a turbine blade shank - Grela, Witold; Burczyński, Tadeusz (Computer Assisted Methods in Engineering and Science, 2005)
The paper describes shape optimisation of a turbine blade shank. The turbine blade shank zone with a compound fillet is a critical location where a high risk of failure exists. The APDL language operating in Ansys .environment is used to write a parametric turbine blade shank FEM models generator, which is a basic part of evolutionary optimisation routine. The goal of the optimisation is the 1st principal stress reduction with maximum allowable mass constraint imposed. Parameterisation routine and optimisation results are presented and discussed.